Europe in Green. European Environmental Democracy. - Parola, Giulia (De Gruyter, 2013)
The book is a cornerstone in the studies aimed at introducing a new form of democracy not just at a global level, through international environmental law, but also at local one, by regional and national regulation, to manage global and local ecological problems. In the light of the results pointed out in Parola's book (Environmental democracy at Global Level. Rights and duties for a new citizenship), this second work examines environmental democracy at a local level by referring to EU law. The European Union, as the only global region with the official objective of simultaneously promoting economic development, social cohesion and environmental protection is here used as an example for analyzing how the region has found (and is still developing) a range of solutions to various environmental issues. The book sheds new light on the transformation of Europe into a Green Europe.
Keywords: Environmental law.; LAW / International.; European Law; Environmental law; Electronic books.